Factors affecting Afghan EFL undergraduates' speaking skill / Hazrat Usman Mashwani - Mashwani, Hazrat Usman (2018)
Reading, writing, listening and speaking are the four primary and required skills of every language. Of the four skills of a language, speaking is the skill that always matters the most for a language learner, and it is considered essential. According to Nazara (2012), speaking is an important and essential skill of the four language skills, and as an EFL student, one needs to master the speaking skill. However, the majority of Afghan EFL undergraduates face difficulties in this all-important skill of the language. According to Zia and Sulan (2015), for most of Afghan undergraduate EFL learners, reading and writing are easy, but in oral communication, they are not accurate and fluent. Hence, this study was conducted to investigate the factors that affect the Afghan undergraduate EFL learners' speaking skill at Sayed Jamaluddin Afghani University Kunar, Afghanistan. The study investigated the factors that affect the students' speaking skill in three inter-related areas, i.e., the teacher, the student and the classroom environment. A mixed method was used for this study, i.e., quantitative (questionnaire) as well as qualitative (interview). The data of the questionnaire was descriptively analysed in SPSS version 20 and presented in figures and tables. The interview data were thematically analysed and presented. A total of 90 students (40 junior and 50 senior) were purposively selected and participated in this study. The findings revealed that the rare use of speaking activities like pair work, group work, role-plays, group presentations and improper method of teaching were some of the factors on the part of teachers that affected students' speaking skill. Psychological factors and weak background of English language on the part of students were some of the factors that impede students speaking skill. Similarly, large classes and the lack of basic facilities in the speaking classroom were some of the factors on the part of learning-environment that affected the students speaking skill. It is hoped that the findings of the current study will help teachers as well as students to be attentive toward their related responsibilities to reduce the factors that affect students' speaking skill.